Joint together: The etiology and pathogenesis of ankylosing spondylitis - Xiong, Yuehan; Cai, Menghua; Xu, Yi; Dong, Peng; Chen, Hui; He, Wei; Zhang, Jianmin (Frontiers in Immunology, 2022)
Ankylosing spondylitis (AS) is a chronic autoimmune disease that mainly involves the spine and sacroiliac joint, leading to loss of flexibility and fusion of the spine. Compared to other diseases related to spondyloarthritis (SpA), AS has a very distinct hereditary disposition and pattern of involvement, and several hypotheses about its etiopathogenesis have been proposed. In spite of significant advances made in Th17 dynamics and AS treatment, the underlying mechanism remains concealed. To this end, we covered several topics, including the nature of the immune response, the microenvironment in the articulation that is behind the disease’s progression, and the split between the hypotheses and the evidence on how the intestine affects arthritis. In this review, we describe the current findings of AS and SpA, with the aim of providing an integrated view of the initiation of inflammation and the development of the disease.